A young girl with suspected encephalitis caused by avian influenza A (H5N1) infection in Indonesia - Juniatiningsih, Anita; Setyanto, Darmawan B; Setiawaty, Vivi; Sedyaningsih, Endang R (Paediatrica Indonesiana, 2010)
A previously healthy two-year-old girl was admitted to the Emergency Unit of Cipto Mangunkusumo Hospital (CMH) Jakarta, on March 23, 2006 with a deterioration of consciousness since four days before admission. She was referred by a district hospital with a working diagnosis of suspect encephalitis, gastroenteritis, and febrile convulsion. History taken from her parents revealed that since eight days before admission she had a mild fever and cough, without rhinorrhea. Her appetite, defecation and urination were normal. Patient was taken to a clinic, where she was diagnosed as having an upper respiratory tract infection, and was given three kinds of medicine (i.e., antipyretic, expectorant and antibiotic).